PENGARUH LOCUS CONTROL, E-MONEY DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SLAMET RIYADI SURAKARTA - Salsa Dila Septiani Saputri; Suprihatmi Suprihatmi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study is a survey research conducted on Students of the Faculty of Economics dan Business, Slamet Riyadi University, Surakarta. The purpose of this study is to examine the influence of locus of control, e-money, dan financial literation on consumptive behavior. The type of data used is quantitative, dan the data source is primary data. Data collection was carried out by distributing questionnaires to the relevant respondents. The population in this study consists of Students of the Faculty of Economics dan Business, Slamet Riyadi University, Surakarta. The sampling technique used was proportional rdanom sampling, resulting in a sample of 96 respondents. The data were collected using questionnaires that had been tested for validity dan reliability. The data analysis techniques used include multiple linear regression, t-test, F-test, dan the coefficient of determination (R²).The results of the study show that locus of control has a significant effect on the consumer behavior of students of the Faculty of Economics dan Business Slamet Riyadi University Surakarta. E-money has a significant effect on the consumer behavior of students of the Faculty of Economics dan Business Slamet Riyadi University Surakarta. Financial literacy does not have a significant effect on the consumer behavior of students of the Faculty of Economics dan Business Slamet Riyadi University Surakarta. The coefficient of determination (adjusted R square) is 0.621, meaning that locus of control, e-money dan financial literation contribute 62.1% to consumptive behavior.